Falls among people with bilateral vestibulopathy: A review of causes, incidence, injuries, and methods - Herssens, Nolan; How, Daniella; van de Berg, Raymond; McCrum, Christopher (JAMA otolaryngology - head & neck surgery)
People with bilateral vestibulopathy experience severe balance and mobility issues. Fear and anxiety are associated with reduced activity, which can further affect balance and fall risk. Understanding and intervening on falls in this population is essential. The aims of this narrative review are to provide an overview of the current knowledge and applied methods on fall incidence, causes, and injuries in bilateral vestibulopathy. OBSERVATIONS Eleven articles reporting falls incidence in people with bilateral vestibulopathy were deemed eligible, including 3 prospective and 8 retrospective studies, with a total of 359 participants, of whom 149 (42%) fell during the assessed period. When reported, the most common perceived causes of falls were loss of balance, darkness, and uneven ground. Information on sustained injuries was limited, with bruises and scrapes being the most common, and only 4 fractures were reported. As most studies included falls as a secondary, descriptive outcome measure, fall data obtained using best practice guidelines were lacking. Only 6 studies reported their definition of a fall, of which 2 studies explicitly reported the way participants were asked about their fall status. Only 3 studies performed a prospective daily fall assessment using monthly fall diaries (a recommended practice), whereas the remaining studies retrospectively collected fall-related data through questionnaires or interviews. While most studies reported the number of people who did and did not fall, the number of total falls in individual studies was lacking. CONCLUSIONS AND RELEVANCE The findings from this review suggest that falls in people with bilateral vestibulopathy are common but remain an understudied consequence of the disease. Larger prospective studies that follow best practice guidelines for fall data collection with the aim of obtaining and reporting fall data are required to improve current fall risk assessments and interventions in bilateral vestibulopathy.